Theological Influences on Slaughter Techniques: Convergence and Divergence in Halal and Kosher Certification - Prasetianti, Isnaeni Gelda; Kuswanjono, Arqom (Universitas Islam Indonesia, 2024)
This study aims to analyze the influence of theology on the slaughter techniques applied in the two traditions, as well as to see how the differences and similarities in these religious teachings contribute to the development and application of halal and kosher certification in the food industry. The study uses a qualitative approach with a literature study method, which involves analyzing academic literature, fatwa documents, halal/kosher guidelines, and certification standards. The results show that both traditions share similarities in the use of sharp tools, thorough bloodletting, and respect for animal welfare, reflecting adherence to ethical and spiritual principles. However, there are fundamental differences, such as the prohibition of stunning in kosher, and the role of the shochet as a trained slaughterer in the Jewish tradition. Halal and kosher certification play an important role in ensuring adherence to religious principles amidst the challenges of mass production in the modern food industry. Despite these obstacles, both traditions continue to emphasize the balance between spiritual and ethical needs in food consumption, making the principles of animal welfare and food safety a top priority in maintaining the integrity of religious values in the modern era.